A Study on Neurological Diseases like Alzheimer’s, Dementias, its Causes and an attempt To Develop a Rule-Based Expert System - Girish, TM; Sing, Vivek Kumar; Sreekantha, DK (International Journal of Computer Sciences and Engineering, 2025)
Dementia is a general term for a gathering of brain disorders. Alzheimer's disease is the most widely recognized sort of dementia, representing 60 to 80 percent of cases. This fact sheet quickly talks about Alzheimer's and some different dementias. A wide range of dementia includes mental decrease that: Influences more than one of the following four core mental abilities Recent memory, Language, Visuospatial function, Executive capacity. The paper likewise introduces a Rule-based Expert System for Memory Loss Disease with the assistance of principles and truths. It is an endeavor to concentrate on some of critical illnesses identified with memory loss like Alzheimer's disease, Parkinson's disease, Huntington's disease and dementia which are among the most widely recognized sorts of memory loss diseases. This Expert System will help the patients to get the required guidance about the diverse issue assault to them because of their nervous system disorders. The expert rules were developed on the symptoms of each type of neurological disease, and they were presented using decision tree and inferred using forward-chaining method. The knowledge base comprises of data about the memory loss and all the diseases related to it identified with it which is gathered from books and specialists (area specialists) about neurology and its disorders.